Development of an Inquiry-Based Worksheet to Practice Cognitive and Science Process on Light Wave Concepts - Firdaus, Ikmal Sofil; Efendi, Ridwan; Sinaga, Parlindungan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This study aims to develop inquiry skills science worksheets to practice cognitive abilities and science process skills. The research used R&D with ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants of this research consisted of lecturers, teachers, and students. The research sample consisted of two XI classes as experimental and control classes. The feasibility of the worksheet was analyzed by content validity index (CVI), the improvement of cognitive abilities and science process skills was analyzed using N-Gain, the effectiveness of the worksheet to practice cognitive abilities and science process skills was analyzed using cohen'd effect size, and student responses were analyzed using descriptive quantitative. The overall feasibility of the science inquiry skills worksheet was declared "Feasible" from all aspects of science inquiry skills. The increase in cognitive abilities after learning using the sheet is 0.34 which is included in the moderate category. Meanwhile, the increase in science process skills after learning using worksheets amounted to 0.51 which is included in the moderate category. The effectiveness of worksheets to practice cognitive abilities has a score of 0.53 which is included in the medium criteria. Meanwhile, the effectiveness of worksheets to practice science process skills has a score of 0.63 which is included in the medium category. Students' responses to the inquiry skills science worksheets in terms of interest, pleasure, and convenience have good responses. The worksheets developed are valid and feasible to use as learning tools that support inquiry-based learning and improve cognitive abilities and science process skills in light waves material.